2010
DOI: 10.1016/j.hrthm.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Early afterdepolarizations and cardiac arrhythmias

Abstract: Early afterdepolarizations (EADs) are an important cause of lethal ventricular arrhythmias in long QT syndromes and heart failure, but the mechanisms by which EADs at the cellular scale cause arrhythmias such as polymorphic ventricular tachycardia (PVT) and Torsades de Pointes (TdP) at the tissue scale are not well-understood. Here we summarize recent progress in this area, discussing i) the ionic basis of EADs, ii) evidence that deterministic chaos underlies the irregular behavior of EADs, iii) mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
287
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(298 citation statements)
references
References 38 publications
(43 reference statements)
10
287
1
Order By: Relevance
“…Following that, we also measured the early after-depolarization (EAD) and autonomous action potentials (APs), two hallmarks of cardiac arrhythmias. 15,16 Our data showed the occurrence of EAD in exon 33…”
Section: Exon 33mentioning
confidence: 61%
“…Following that, we also measured the early after-depolarization (EAD) and autonomous action potentials (APs), two hallmarks of cardiac arrhythmias. 15,16 Our data showed the occurrence of EAD in exon 33…”
Section: Exon 33mentioning
confidence: 61%
“…As expected, Ru360 reduced mitochondrial Ca 2+ uptake. The mechanism of reduced EADs with Ru360 appeared to be reduced sarcolemmal NCX current, a key depolarizing current known to be involved in EADs 2. This effect is most easily explained by Ru360 reducing mitochondrial Ca 2+ loading, reducing mitochondrial Ca 2+ efflux, and decreasing sarcolemmal NCX.…”
Section: Discussionmentioning
confidence: 95%
“…As a first step we explored the changes in AP and individual currents induced by three representative drugs (one taken from each one of the CiPA TdP risk categories), using pharmacology data as used in Li et al (2017). Since it is known that the subtle balance between inward (such as INaL and ICaL) and outward (such as IKr, IKs, IK1, and Ito) currents underlies the generation of EADs, a mechanistic precursor to TdP (Vos et al, 1995;Volders et al, 2000;Wu et al, 2002;Weiss et al, 2010), we also examined the net current between inward and outward currents (Inet) in addition to individual currents. (Crumb et al, 2016); using the block suggested in the ORd paper of 90% INaL block (O'Hara et al, 2011), the sum of squares error is of 38.48, changing the average error to 48.70. using our optimized model.…”
Section: Candidate Metricsmentioning
confidence: 99%
“…Based on ideas from non-linear dynamic theory and studies demonstrating mechanisms of EAD generation (Guo et al, 2007;Weiss et al, 2010;Xie et al, 2010;Chang et al, 2013;Kurata et al, 2017), we established a theoretical framework to quantitatively evaluate the physiological consequences of the change of the qNet (and in principle any) metric. A key concept here is the system robustness (Kurata et al, 2008), which is defined as the level of a specific perturbation the system can tolerate without a qualitative change of stability (e.g., emergence or annihilation of oscillations).…”
Section: Qnet Correlates With the System's Robustness Against Eadsmentioning
confidence: 99%